The Use of Restaurant Organic Waste Flour as a Substitute for Concentrate in Joper's Chicken Feed - Dedi Suryanto; Usman Ali (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2022)
The purpose of the study was to analyze body weight gain and the efficiency of feed use in the maintenance of Joper chicken using restaurant organic waste (ROW) as a substitute for concentrated feed. The research material was 75 male Joper free-range chickens aged 1.5 month with initial weight of 0.57 – 0.80 g/head with a coefficient of diversity 9.25%. The feed ingredients were ground corn, rice bran, concentrate, commercial feed and dry milled ROW. The equipment for cages was for feeding, drinking, and weighing. The study was conducted for 30 days with experimental methods and a completely randomized design consisting of 5 treatment feeds, repeated 3 times, and each experimental unit filled with 5 heads. Substitution with concentrate in feed can improve performance and feed efficiency in Joper chickens. The results showed that the use of 60% ROW (T4) as a substitute for concentrate feed had a significant effect (P<0.05) on increasing feed conversion ratio and efficiency in Joper native chickens. On the other result, significant increase on (P<0.05) body weight gained because of feed containing 40% concentrate (T1), rather than the feeds with containing ROW materials. This means that the use of organic waste from restaurant 60% or 24% in feed as concentrate substitute optimally increased feed efficiency and body weight gain of Joper native chicken.